Методики расчета активных фильтров на неидеальных операционных усилителях - Дёмин, А. Н. (ХНУРЭ, 2009)
Nowadays filters, that mcluds operating amplifiers obtains wide application in analogic schemetechnics. For calculation element’s nominals of high frequency filters it is necessary to take into consideration unideality of operating amplifiers. This work describes methods and results of calculation element’s nominals different typing filters with accounting unideality OA
Keywords: операционный усилитель; методики расчета активных фильтров